Teknologi Kantor Di Era Digital: Mengulas Alat-Alat Modern Untuk Produktivitas Yang Lebih Baik Dan Memilih Peralatan Kantor Yang Ergonomis Untuk Kantor Yang Lebih Sehat - Fitri Nur Waliyaden; Gloria Theodora Wahi Leo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of digital technology has significantly changed the work paradigm, creating a work environment that is not bound by geographical boundaries through the utilization of cloud platforms, online collaboration tools, and advanced digital communications. This transformation increases productivity and enables collaboration between employees, even if they work in different locations. However, these changes also bring new challenges related to employee well-being. One of the main issues is stress due to the blurring of working time boundaries, with employees often struggling to distinguish between work and personal time. In addition, there is an increased risk of physical injury due to the use of non-ergonomic digital devices, including injuries from improper keyboard and mouse use. To overcome these challenges, companies must implement ergonomic office equipment to support the physical and mental health of their employees. Modern technology, including artificial intelligence (AI), plays an important role in selecting and customizing ergonomic office equipment to the individual needs of employees. AI analyzes equipment usage and posture data and recommends adjustments to prevent injuries and improve work comfort. The purpose of this study is to discuss the importance of office technology and ergonomics in improving employee productivity and well-being. By integrating advanced technology and ergonomic principles, companies can create a more comfortable and healthy work environment. This not only increases productivity, but also improves job satisfaction, creativity and employee retention. An ergonomic work environment reduces stress and fatigue, allowing employees to work more effectively and efficiently. The research method used in this study is a literature review that collects and analyzes information from various sources regarding office technology, ergonomics, and their impact on work productivity. The study found that the use of ergonomics-enabled technology in the workplace significantly increases employee happiness. Companies that invest in ergonomic technology and equipment can create a sustainable competitive advantage through a healthier and more productive workforce. This study shows that a balance between technology and ergonomics is key to creating a productive and sustainable work environment.